TEACHING SPEAKING ABILITY OF VOCATIONAL HIGH SCHOOL STUDENTS THROUGH DIRECT INSTRUCTION MODEL - Etty Pratiwi; Puspa Oktalia; Dewi Kartika Sari (Esteem Journal of English Education Study Programme, 2024)
Through the use of oral tests to describe places described in descriptive texts, this study sought to investigate the efficacy of an instruction model combined with a learning model in enhancing the speaking abilities of Vocational High School (SMK) students. The goal of this study was to teach English speaking skills in a classroom setting. An experimental strategy with a pre- and post-test one group design was employed in the research methodology. Tenth grade TKJ students from Vocational High School PGRI Pangkalan Balai academic years 2023/2024 made up the research sample. Speaking exams were used to gather data both before and after the course of treatment. The speaking exam was divided into multiple parts, including fluency, grammar, vocabulary, and pronunciation. With an average pre-test score of 47.23% and an average post-test score of 64.3, the data analysis results demonstrated a considerable improvement in the speaking ability of students who received instruction through a direct instruction paradigm. This result demonstrates how well the learning model with direct instruction worked to enhance the speaking skills of students enrolled in vocational programs.